PENGARUH KOMPETENSI SUMBER DAYA MANUSIA TERHADAP IMPLEMENTASI ANGGARAN YANG BERBASIS KINERJA - Lestari Gowasa; Subhilhar Subhilhar; Agus Suriadi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2020)
The purpose of this study is to determine the effect of human resource competence on the implementation of performance-based budget in the Regional Financial Management Agency of North Nias Regency. The research method used in this research is the method of mixed methods, that is the combination of qualitative and quantitative research. The sample in this study amounted to 35 respondents. Based on purposive sampling. The location of this research is at the Regional Financial Management Agency of North Nias Regency. The result of the research shows that the competence of human resources bepengaruh positive and significant to the implementation of performance-based budget in the Regional Financial Management Agency of North Nias Regency with a value of 0.896 which means the correlation or the relationship between the variables of human resource competence to the implementation of performance-based budget has a strong relationship and is positive.